Pemanfaatan Teknologi Informasi untuk Meningkatkan Penjualan Produk UMKM Melalui Digital Marketing di Kelurahan Keranggan, Setu, Tangerang Selatan - Irmal, Irmal; Sutoro, Muh.; Khair , Oki Iqbal (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
Micro, Small, and Medium Enterprises (MSMEs) or commonly known as SMEs, are an important sector in the Indonesian economy, especially in the Kel. Keranggan area of South Tangerang. In this digital era, the use of information technology, especially digital marketing, is the key to increasing MSME product sales. This paper aims to analyze the use of information technology to increase MSME product sales with digital marketing in a particular area. This research uses a qualitative descriptive method with a case study in a particular area. Data were collected through direct interviews with UMKM actors, document analysis, and field observations. The results of the study show that the use of information technology for digital marketing has a positive impact on the sales of UMKM products in the Kelurahan Keranggan area. Digital marketing helps businesses reach a wider market, increase brand awareness, and build better relationships with their customers. The use of information technology with digital marketing is an effective strategy to increase UMKM product sales. There is a need for ongoing training and mentoring for UMKM actors so that they can utilize information technology effectively and efficiently.